Gestão dos resíduos plásticos pós-consumo: perspectivas para reciclagem no município de Pau dos Ferros/RN - Cavalcante, Rebeca Araújo Sousa (Universidade Federal Rural do Semi-Árido, 2016)
As plastic bags have proven to be one of the great villains to the environment. From the 1970s to the present day, they have become very popular in the free distribution of supermarkets and trade in general, and is a cheap form of advertising. They are widely used also without packing household waste for collection. They are made of polyethylene or polypropylene, materials derived from petroleum or natural gas, non-renewable energy source. Analyzing the life cycle of plastic bags, especially the city of Pau dos Ferros / RN, noted that the elastic relate to their environment from manufacture when the extraction of its raw material oil or gas natural, Where is heating to high temperatures and the release of gases that cause greenhouse effect, contributing to global warming, as well as its own disposal, are the same decaying, harmful particles to the environment that contaminate the soil are released. There are some bibliographic and field research, interviews and questionnaires, a better understanding qualitatively and quantitatively the current scenario of the municipality in relation to the management of waste from schools that are discarded. Present alternatives to the correct disposal of plastic bags in the environment in order to minimize environmental impacts through the public awareness of the selective collection and recycling.
Keywords: Sacolas plásticas; Gestão de resíduos; Impactos ambientais; Plastic bags; Waste management; Environmental impacts; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA